"O brilho sinistro da estrela vermelha": uma análise do anticomunismo em Santa Catarina entre 1946 e 1950 por meio do jornal O Estado - Sobierai, Daniela (2021)
The analysis carried out in the present research focuses on the publications on communism published in the newspaper O Estado between the years 1946 and 1950. During this period, a process of re-democratization post-Estado Novo was taking place in Brazil; and, in the global context, the post-war and the beginning of Cold War. These are relevant periods as they influenced the persecution of the Brazilian Communist Party (PCB) and its supporters. The objective of this study is to elucidate how the theme of communism was approached in the newspaper published in the state of Santa Catarina during the democratic period. For this investigation, content analysis was employed. The newspaper O Estado was owned by Aderbal Ramos da Silva and was used to expose ideas of the Social Democratic Party (PSD). Due to its party connection, the periodical became a tool for publicizing the government, since President Eurico Gaspar Dutra was also a member of the party and served as the main persecutor of the Brazilian Communist Party. It is concluded that the newspaper published anti-communist discourses because there was a political tradition that existed since the Communist Uprising and also because there was a real threat of communist actions, as these gained notoriety as of the 1945 elections. For this reason, O Estado issued speeches to disqualify its communist opponents, who were not gain space in the region of Santa Catarina because they were foreigners and were planning the destruction of the country, religion, and family structure. Furthermore, it was necessary to warn the population about this “threat” that was hounding the Brazilian territory.